The effect of induced defecation technique with deep colonic precision localization in patients with complex constipation (结肠精准定位诱导排便技术在复杂性便秘患者中的应用研究) - ZHAO Jihong (赵继红); JIANG Yunlu (姜蕴璐); JI Jie (纪婕) (Association of Integrative Nursing, 2023)
Objective To investigate the effect of induced defecation technique with deep colonic precision localization in patients with complex constipation. Methods Fifty-three patients with complex constipation who were admitted to and consulted by the Department of Rehabilitation Medicine Center from November 2021 to May 2022 were recruited as research subjects. All patients received induced defecation with deep colonic precision positioning, and intervention effect was analyzed, Results The colonic deep-precision positioning induced defecation technique was reported to significantly relieve abdominal discomfort, bloating, constipation, diarrhea, and other intestinal disorders in 53 individuals with complex constipation. After the intervention, the patients had defecation in 49 (92. 45%)cases and no defecation in 4 (7. 55%)cases; 51 (96. 23%) cases and no defecation in 2 (3. 77%)case after the intervention; abdominal symptoms improved in a total of 53 (100. 00%)cases. The Wexner constipation score of the patients after the intervention was significantly lower than that before the intervention (P＜0. 05). Conclusion On patients with difficult constipation, the approach of induced defecation with deep colonic precision positioning provided considerable therapeutic benefits and significantly alleviated their clinical symptoms. (目的 探讨结肠精准定位的诱导排便技术在复杂性便秘患者中的应用效果。方法 对2021年11月-2022年5月江苏省人民医院康复医学中心收治及会诊的53例复杂性便秘患者进行结肠精准定位的诱导排便, 评估干预效果。结果 53例复杂性便秘患者在排除禁忌后接受结肠精准定位的诱导排便技术干预, 腹痛、腹胀、便秘、腹泻等肠道问题得到缓解。干预后患者排便49(92. 45%)例、未排便4(7. 55%)例; 干预后排气51(96. 23%)例、未排气2(3. 77%)例; 腹部症状改善共计53(100. 00%)例, 干预后患者Wexner便秘评分低于干预前, 差异有统计学意义(P＜0. 05)。结论 结肠精准定位的诱导排便技术对复杂性便秘患者有明显治疗效果, 能够有效减轻患者临床症状。)